2018
DOI: 10.3390/geosciences8010027
|View full text |Cite
|
Sign up to set email alerts
|

A New Degassing Model to Infer Magma Dynamics from Radioactive Disequilibria in Volcanic Plumes

Abstract: Pb within gas bubbles en route to the surface. Theoretical short-lived radioactive disequilibria in volcanic gases predicted by this new model differ from those produced by the former models and better match the values we measured in the plume during the 2015 campaign. A Monte Carlo-like simulation based on variable parameters characterising the degassing process (magma residence time in the degassing reservoir, gas transfer time, Rn-Pb-Bi-Po volatilities, magma volatile content) suggests that short-lived dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…This observation strongly suggests for the first time that the plume is enriched in radon. Moreover, covariations of radon activity in the air and volcanic activity have been noticed and indicate that radon activity in magmatic gas plumes could also be an interesting parameter to monitor, as was previously proposed by theoretical modeling [ 9 ]. Finally, this study has also revealed very high radon activities (up to 8 kBq/m 3 ) in the air in a few zones of the Mt.…”
Section: Introduction and State-of-the-artmentioning
confidence: 71%
“…This observation strongly suggests for the first time that the plume is enriched in radon. Moreover, covariations of radon activity in the air and volcanic activity have been noticed and indicate that radon activity in magmatic gas plumes could also be an interesting parameter to monitor, as was previously proposed by theoretical modeling [ 9 ]. Finally, this study has also revealed very high radon activities (up to 8 kBq/m 3 ) in the air in a few zones of the Mt.…”
Section: Introduction and State-of-the-artmentioning
confidence: 71%
“…Our code will also be made available in the open-source form for the community to enhance. Besides improving the plume model, coupling the volcanic plume model with magma reservoir models (e.g., Terray et al, 2018), which could provide more accurate eruption conditions, might improve accuracy of the volcanic plume simulation.…”
Section: Discussionmentioning
confidence: 99%
“…The cloud microphysics predicts the mass of hydrometeors in liquid and ice phases (Herzog et al, 1998). Additional modules, including gas-phase chemistry (Trentmann et al, 2002) and gas scavenging by hydrometeors (Textor et al, 2003), were added lately. A further extension was made to include particle aggregation (Textor et al, 2006b, a).…”
Section: Existing Plume Modelsmentioning
confidence: 99%
“…The cloud microphysics predicts the mass of hydrometeors in liquid and ice phases . Additional modules, including gas-phase chemistry (Trentmann et al, 2002) and gas scavenging by hydrometeors (Textor et al, 2003), were added lately. A further extension was made to include particle aggregation (Textor et al, 2006b, a).…”
Section: Existing Plume Modelsmentioning
confidence: 99%